Challenges and conducts for breastfeeding in premature babies: an integrative review (Research, Society and Development, 2022)
The research aims to understand and clarify the challenges and the conducts to be taken to establish breastfeeding in premature babies. This research was carried out using the integrative literature review method, the preparation of a methodological survey for the research was carried out in the period of April 2022, the databases used were the Latin American and Caribbean Literature in Health Sciences (LILACS), Medical Literature Analysis and Retrieval System Online (MEDLINE) and Science Direct using the Health Sciences Descriptors (Decs), they being "Premature Newborn", "Breastfeeding", and "Pediatrics", these crossed through the Boolean operator AND. The inclusion criteria adopted were: studies that answered the research question, period of publication (2015-2022), being in Portuguese, English or Spanish. The duplicates, integrative reviews, books, letters to the editor and previous-note articles were excluded, totaling 9 articles to compose the study. It was possible to identify the difficulties that occur during the breastfeeding process for premature newborns, the possible challenges for mothers during this stage, It was also noticed that the literature is scarce as to the importance of the discussion of this theme in the present day. Finally, it is concluded that the study was intended to direct attention to the neonatal care of premature babies, however, the research process of the literature was somewhat scarce, thus showing the fragility of the domain on the subject in the present day, which promotes the encouragement of new research on the subject.